Handbook of research on clinical applications of computerized occlusal analysis in dental medicine - Kerstein, Robert B. (IGI Global, 2020)
"This book explores the use of digital tools in dentistry, including their evolution as well as evidence-based research on the benefits of technological tools versus non-digital occlusal indicators"--Provided by publisher.